The Effect of Leverage, Profitability, Sales Growth, and Capital Intensity on Tax Avoidance in Property and Real Estate Companies - Asri Zaldin; Hubertus Maria Rosariandoko Wijanarko (Journal of E-business and Management Science, 2023)
This research aims to determine the factors influencing tax avoidance in property and real estate listed companies in Indonesia. The population in this research is property and real estate listed companies in Indonesia. This research used 11 property and real estate listed companies registered in Indonesia for three years from 2019-2021, resulting in a sample of 33 companies studied. The sample collection method is library research and field research by collecting data on financial reports of property and real estate listed companies for the 2019-2021 period. The data was analyzed using multiple linear regression analysis using SPSS Software version 25. The research results show that the variables that influence tax avoidance are leverage and profitability, while the variables that do not influence tax avoidance are capital intensity and sales growth. It recommended that supervision be carried out regarding tax avoidance practices because the rise of tax avoidance causes state revenues to be less than optimal.